P-LUM-13: Endoscopic ultrasound-guided fine needle aspiration of adrenal lesions: A single-center experience of eighty cases - Bansal, Rinkesh (Endosc Ultrasound, 2017)
BACKGROUND AND OBJECTIVES: It is difficult to get tissue diagnosis from the adrenal glands by radiological imaging, particularly from left adrenal due to their anatomic location. Endoscopic ultrasound-guided offers less invasive mode of fine needle aspiration (FNA) due to proximity to adrenals. The aim of this study was to evaluate the diagnostic yield of EUS-FNA of adrenal lesions. METHODS: It was a retrospective study conducted from October 2010 to September 2016 at a single tertiary care center in Delhi-National Capital Region. We analyzed data of eighty patients with adrenal lesions, in whom EUS FNA was performed. RESULTS: Of the eighty patients, mean age was 56 ± 12.2 years; there were 63 males. Indications of FNA were pyrexia of unknown origin (n = 52), evaluation for metastasis (n = 18), and incidentally detected adrenal enlargement (n = 10). FNA were taken from left adrenal in seventy patients by transgastric route, while in ten patients, FNA was taken from right adrenal using transduodenal route. Technical successes and diagnostic adequacy of specimen were achieved in 100% cases. A 19-gauge needle was used in majority (80%). Median number of passes was 3. The cytopathological diagnoses were tuberculosis (n = 36), histoplasmosis (n = 13), metastatic lung carcinoma (n = 10), adrenal adenoma (n = 9), hepatocellular carcinoma (n = 4), carcinoma gall bladder (n = 2), lymphoma (n = 2), endometrioid carcinoma (n = 1), neuroendocrine tumor (n = 1), adrenal lipoma (n = 1), and adrenal myelolipoma (n = 1). No procedure-related adverse events were reported. CONCLUSIONS: EUS-FNA is a safe and effective method for evaluating adrenal lesions.